Effect of Dietary Intake and Lifestyle Patterns on Glycaemic Response among People with Type 2 Diabetes Mellitus in Manipur, India - Mongjam Priyangka Chanu; Namita Singh (Disease and Health: Research Developments Vol. 2, 2024)
Background: Diabetes is a chronic disease that occurs either when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. Its increasing prevalence in India is closely linked to aging populations, more urban lifestyles, and shifts in demographic structures. Objectives: The aim of the study was to examine the association between dietary intake and lifestyle patterns of diabetes patients in Manipur. Materials and Methods: Tribal and nontribal respondents between 45-64 years of age were randomly selected from the Regional Institute of Medical Sciences (RIMS) Hospital Manipur. A total number of 200 study subjects, 100 tribal and 100 nontribal subjects constituted the study. The chosen age range falls into late middle age (45–64 years old). The information was collected on the socio-demographic profile, clinical, and anthropometric measurements and dietary intakes of the patients by using interview schedules and 24-hour dietary recall methods. The data were analyzed and tabulated using statistical tools such as frequency, percentage, mean, standard deviation and Pearson’s correlation test. Results: The key results indicate that alcohol consumption, elevated triglyceride levels, low energy, oils and sugar intake were notably linked with the prevalence of diabetes. Additionally, low calcium intake, particularly among nontribal individuals, demonstrated a significant correlation with elevated Fasting Blood Glucose (FBG) levels, suggesting a potential risk factor for Type 2 diabetes. Moreover, low calcium intake among the non-tribal community was associated with increased Post Prandial (PP) test results, indicating a rise in post-meal glucose levels. Conclusion: Notably, tribal energy intake and non-tribal protein consumption were significantly associated with HbA1c levels, reflecting their impact on glycemic response. Moving forward, further research and targeted public health strategies are warranted to comprehensively address the multifaceted nature of diabetes prevalence and management within these communities.